2005
DOI: 10.3748/wjg.v11.i32.4939
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 and MUC5AC mucin expression in liver fluke-associated intrahepatic cholangiocarcinoma

Abstract: MUC1 is overexpressed in liver fluke-associated cholangiocarcinoma and relates to vascular invasion and poor prognosis, whereas MUC5AC mucin is neoexpressed and relates to neural invasion and advanced ICC stage. High MUC1 expression in tumor may be useful for predicting the poor outcome of ICC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 50 publications
3
36
0
Order By: Relevance
“…Overexpression of MUC5AC in PDA has been reported in 70% to 100% of the cases in several studies [13,14,25]. Similarly, a high frequency of MUC5AC expression has been reported in cholangiocarcinoma [11,13,14,[26][27][28][29] and gallbladder adenocarcinoma [11,15]. In the studies where ICC and extrahepatic cholangiocarcinoma (ECC) were separately evaluated, it was apparent that ECCs more frequently expressed MUC5AC than ICCs.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of MUC5AC in PDA has been reported in 70% to 100% of the cases in several studies [13,14,25]. Similarly, a high frequency of MUC5AC expression has been reported in cholangiocarcinoma [11,13,14,[26][27][28][29] and gallbladder adenocarcinoma [11,15]. In the studies where ICC and extrahepatic cholangiocarcinoma (ECC) were separately evaluated, it was apparent that ECCs more frequently expressed MUC5AC than ICCs.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding, another study showed that MUC1 expression was not associated with histological subtypes in OV-associated Thai ICCs. 42 We also identified genes expressed differentially between MF-type and periductal infiltrating-type ICCs. Notably, IQGAP1 was in the list of genes relatively enhanced in periductal infiltrating-type ICCs compared with MF-type ICCs.…”
Section: Discussionmentioning
confidence: 99%
“…Of the nine studies that have examined the prognostic value of MUC1 in CC, all except one have demonstrated a significant correlation between MUC1 expression and decreased survival, both on univariate and multivariate survival analyses (61,62,(101)(102)(103)(104)(105)(106)(107).…”
Section: Muc1mentioning
confidence: 99%